# SOLUCION PRIMER TALLER

1.

1 1 2+2 4
+ =
= =1
2 2
4
4

2.

1 1 1+ 2 3
+ =
=
2 1
2
2

3.

1 1 4−2 2 1
− =
= =
2 4
8
8 4

4.

1 1 1
+ =
8 9 72

5.

10
4
2 = 10 = 5
1
8 4

6.  1 + 4  + 1 =  2 + 8  + 1 = 10 + 1 = 20 + 4 = 24 = 3 = 3

8
8 1
2 2 2  4  2 4 2
7.

1
10
4 = 3
3
40

8.  4 − 1  + 3 
 4 2 10 


=
6
5
2

 8 − 4  3 
 8  + 10 


=
6
5
2

2

64
 4  3   40 + 24 
 80
 8  + 10  
80

=
 = 6 = 320 = 80 = 40 = 20 = 16 = 2
6
6
5
480 120 60 30 15 3
5
5
2

9.  4 2 + 2  = 16 + 2  =  48 + 2  =  50  = 2500
3 
3  3   3 
9

X=

1 16
+
2 3

CALCULA EL VALOR DE LA INCOGNITA (X)
3 + 32
X=
6
X=

35
6

1.

2.

3

12 + 
2

=1
X
3

12 + 
2
=
=X
1
 24 + 3 

2 

=
=X
1
27
27
20
= 2 =
18 x1 − 10 2=
2

3. 2 x + 3 x − 16 = 20
20
+ 10
==218
x x+ =3x 2= 20
+ 16
= 5 x = 36
36
== x18=x = 20 + 20
5
2
4. 3 x + 4 = 29
40
= 18 x =
= 3 x = 292− 4
= 3 x = 25
25 40
x=
= x =3 2
18

5.

=x=

40
36

=x=

20
18

=x=

10
9

6.

( x ) 2 + 4 = 16
= ( x ) = 16 − 4
2

= ( x ) = 12
2

= x = 12
= x = 3,48
DETERMINAR FUNCIONES
1.

f ( 0) = ( x ) − ( x ) + 6
3

2

= f ( 0 ) = 03 − 0 2 + 6
3
2
f ( − 2 ) = ( − 2) − ( − 2 ) + 6

= f ( 0) = 6
= f ( − 2 ) = ( − 8) − ( − 4 ) + 6
= f ( − 2) = −8 − 4 + 6
= f ( − 2) = −12 + 6
= f ( − 2) = −6

f ( a) = ( a) − ( a) + 6
3

2

= f ( a) = a + 6
2.

f ( 3) =

(3( 3)

−8
3 −1

= f ( 3) =
f ( 3) =

2

)

( 3( 9) − 8)
3 −1

27 − 8
2

19
2
2
3( − 1) − 8
f ( − 1) =
−1−1 2
3( x − 2 ) − 8
f ( x − 2) =
( 3(1( )x−−82) ) − 1
= f ( − 1) =
−1−1
( 3( x − 2)( x − 2) − 8)
= f ( x − 2) =
3 − 8 ( x − 2) − 1
= f ( − 1) =
−2
3 x 2 − 2x − 2x + 4 − 8
= f ( x − 2) =
− 5 5 ( x − 2) − 1
= f ( − 1) =
=
−2 2
= f ( 3) =

(

)

(

)

((

= f ( x − 2) =

(3( x

) )

) )

− 4x + 4 − 8
( x − 2) − 1

2

= f ( x − 2) =

3 x 2 − 12 x + 12 − 8
( x − 2) − 1

= f ( x − 2) =

3 x 2 − 12 x + 4
x − 2 −1

= f ( x − 2) =

3 x 2 − 12 x + 4
x−3

3.

f (1) = 3(1) − (1)

2

= f (1) = 3 − 1
= f (1) = 2

f ( − 2 ) = 3( − 2 ) − ( − 2 )
= f ( − 2) = −6 − ( 4)
= f ( − 2) = −6 − 4
= f ( − 2) = −10
1 1 1
f   = 3  −  
h h h
1 3 1
= f = − 2
h h h

2

2